2012
DOI: 10.1002/mc.21992
|View full text |Cite
|
Sign up to set email alerts
|

IL17Agene polymorphisms, serum IL-17A and IgE levels, and hepatocellular carcinoma risk in patients with chronic hepatitis B virus infection

Abstract: Interleukin (IL)-17A plays important roles in hepatitis B virus (HBV)-induced liver diseases. This study aims to investigate IL17A single nucleotide polymorphisms (SNPs) and the predispositions to chronic HBV infection and hepatocellular carcinoma (HCC) risk and the correlations to IL-17A and IgE levels. Three hundred ninety-five chronic HBV patients, 75 HBV infection resolvers, and 174 healthy controls were included. IL17A SNPs rs8193036 (C/T) and rs2275913 (A/G) and serum IL-17A and IgE levels were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 59 publications
(69 reference statements)
2
22
0
4
Order By: Relevance
“…Some studies show that in vitro stimulated T cells from healthy individuals possessing the rs2275913A allele produced significantly more IL-17 than those without the A allele [5]. Other researchers reported that subjects carrying rs2275913GG genotype had higher serum level of IL-17 than those with AA genotype [12]. Using in vitro stimulated PBMCs, we identified that PBMCs with AA genotype excrete significantly higher level of IL-17 than those with GG genotype, and this phenomenon could be observed in both healthy controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that in vitro stimulated T cells from healthy individuals possessing the rs2275913A allele produced significantly more IL-17 than those without the A allele [5]. Other researchers reported that subjects carrying rs2275913GG genotype had higher serum level of IL-17 than those with AA genotype [12]. Using in vitro stimulated PBMCs, we identified that PBMCs with AA genotype excrete significantly higher level of IL-17 than those with GG genotype, and this phenomenon could be observed in both healthy controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy–Weinberg equilibrium was tested for each locus using Markov chain as implemented in Arlequin software version 3.5 [Excoffier and Lischer, ]. Dominant and recessive genetic models were assumed based on previous studies of phenotype effects [Nakayama et al, ; Barrett et al, ; Christensen et al, ; Tayebi and Mohamadkhani, ; Li et al, ]. Haplotype frequencies were estimated using the MLOCUS computer program [Long et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that IL-17A rs2275913 and rs3819024 polymorphisms were correlated with T. pallidum susceptibility to infection. 23,24 Interestingly, another study showed that IL-17A rs2275913 genotypes did not influence the expression levels of IL-17A in serum in patients with colorectal cancer. Therefore, the current study further analyzed haplotype containing rs2275913 and rs3819024 of IL-17 using SHEsis software.…”
Section: Expression Levels Of Chemokine/ Chemokine Receptor Gene Mrmentioning
confidence: 99%